Myeloid Mineralocorticoid Receptor Activation Contributes to Progressive Kidney Disease - Huang, Louis L. (American Society of Nephrology, 2014)
Clinical and experimental studies have shown that mineralocorticoid receptor (MR) antagonists substantially reduce kidney injury. However, the specific cellular targets and mechanisms by which MR antagonists protect against kidney injury must be identified. We used conditional gene deletion of MR signaling in myeloid cells (MR(flox/flox) LysM(Cre) mice; MyMRKO) or podocytes (MR(flox/flox) Pod(Cre) mice; PodMRKO) to establish the role of MR in these cell types in the development of mouse GN. Accelerated anti–glomerular basement membrane GN was examined in groups of mice: MyMRKO, PodMRKO, wild-type (WT) littermates, and WT mice receiving eplerenone (100 mg/kg twice a day; EPL-treated). At day 15 of disease, WT mice had glomerular crescents (37%±5%), severe proteinuria, and a 6-fold increase in serum cystatin-C. MyMRKO, PodMRKO, and EPL-treated mice with GN displayed proteinuria similar to that in these disease controls. However, MyMRKO and EPL-treated groups had a 35% reduction in serum cystatin-C levels and reduced crescent numbers compared with WT mice, whereas PodMRKO mice were not protected. The protection observed in MyMRKO mice appeared to result predominantly from reduced recruitment of macrophages and neutrophils into the inflamed kidney. Suppression of kidney leukocyte accumulation in MyMRKO mice correlated with reductions in gene expression of proinflammatory molecules (TNF-α, inducible nitric oxide synthase, chemokine (C-C motif) ligand 2, matrix metalloproteinase-12), tubular damage, and renal fibrosis and was similar in EPL-treated mice. In conclusion, MR signaling in myeloid cells, but not podocytes, contributes to the progression of renal injury in mouse GN, and myeloid deficiency of MR provides protection similar to eplerenone in this disease.